HYDRODYNAMIC INTERACTIONS OF MULTIPLE SURFACE-PIERCING STRUTS BY SMOOTHED PARTICLES HYDRODYNAMICS - Vernengo G.; De Marco Muscat-Fenech C.; Demirel Y. K.; Gaggero S.; Villa D. (Volume 7: CFD and FSI, 2022)
The hydrodynamics of surface piercing struts and pile-like structures in general presents some very complex fluid dynamics phenomena that are worth investigating. Among them there are the forward wave pile-up at stagnation, the wave breaking with flow reversal like that observed in Bidone-type hydraulic jumps, flow separation caused by interactions of steep free-surface waves and the turbulent wall boundary layer. Such a type of flow structures plays a key role in several engineering applications, ranging from naval architecture to civil and ocean engineering. The hydrodynamic analysis of different surface-piercing struts in tandem configuration has been done in the framework of a Smoothed Particle Hydrodynamic approach available through the open-source software DualSPHysics, developed to exploit the GP-GPU architecture to speed up the computation. A numerical wave tank has been set-up to carry out calm water tests. Beyond the influence of the forward speed, the analysis has focused on the effect of three main geometric parameters establishing the configuration: the longitudinal and the lateral distance among the vertical, surface-piercing, struts and the relative size among them. The mean and the rms values of the unsteady near-field free surface elevation have been analyzed and compared among the selected cases and interaction effects are studied in comparison to the free surface obtained for the equivalent single strut configuration.